Mengaktualisasikan Pendidikan Agama Kristen Anak dalam Pelayanan Misi - Poluan, Deice Miske; Arifianto, Yonatan Alex (SIKIP: Jurnal Pendidikan Agama Kristen, 2023)
The Great Commission as stated in Matthew 28:18-20 gives the mandate and command to every believer to go and make disciples of all ethnic groups of Christ. The phrase all nations certainly includes children, who must be made disciples of Christ. However, children are often forgotten, the focus of evangelism is only on adults. In the context of Christian education, there is Christian religious education for children which specifically educates and serves children. The research explains how to actualize children's Christian religious education in mission service to reach and serve children to be brought to Christ to become His disciples. This research uses qualitative research methods with a literature review approach. The results of this research explain that children's Christian Religious Education is the spearhead in mission services to reach children, children's Christian Religious Education presents the concept of an approach to children, children's Christian Religious Education has a concept of how to disciple children. After this research, the author found that children's Christian religious education can be actualized in mission service to reach and make disciples of every ethnic group of Christ, especially children.  AbstrakAmanat Agung yang tertuang dalam Matius 28:18-20 memberikan amanah dan perintah kepada setiap orang percaya untuk pergi menjadikan semua suku bangsa murid Kristus. Frasa semua bangsa tentunya termasuk anak-anak, yang harus dijadikan murid Kristus. Namun demikian, anak-anak seringkali dilupakan, fokus penginjilan hanya pada orang dewasa. Dalam konteks pendidikan Kristen ada Pendidikan Agama Kristen anak yang secara spesisfik mendidik dan melayani anak. Penelitian menjelaskan bagaimana mengaktualisasikan Pendidikan Agama Kristen anak dalam pelayanan misi untuk menjangkau dan melayani anak-anak untuk dibawa kepada Kristus menjadi murid-Nya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan kajian pustaka. Hasil penelitian ini menjelaskan bahwa Pendidikan Agama Kristen anak merupakan ujung tombak dalam pelayanan misi untuk menjangkau anak-anak, Pendidikan Agama Kristen anak menyuguhkan konsep pendekatan kepada anak-anak, Pendidikan Agama Kristen anak memiliki konsep bagaimana memuridkan anak-anak. Pada kesimpulan penelitian ini, penulis menemukan bahwa Pendidikan Agama Kristen anak dapat diaktualisasikan dalam pelayanan misi untuk menjangkau dan menjadikan setiap suku bangsa murid Kristus secara khusus anak-anak.